High Temporal Resolution 3D Live-Cell Imaging of Budding Yeast Meiosis Defines Discontinuous Actin/Telomere-Mediated Chromosome Motion, Correlated Nuclear Envelope Deformation and Actin Filament Dynamics - Tadasu Nozaki (Frontiers Media S.A., 2021)
Chromosome movement is prominent at mid-meiotic prophase and is proposed to enhance the efficiency and/or stringency of homolog pairing and/or to help prevent or resolve topological entanglements. Here, we combine fluorescent repressor operator system (FROS) labeling with three-dimensional (3D) live-cell imaging at high spatio-temporal resolution to define the detailed kinetics of mid-meiotic prophase motion for a single telomere-proximal locus in budding yeast. Telomere motions can be grouped into three general categories: (i) pauses, in which the telomere “jiggles in place”; (ii) rapid, straight/curvilinear motion which reflects Myo2/actin-mediated transport of the monitored telomere; and (iii) slower directional motions, most of which likely reflect indirectly promoted motion of the monitored telomere in coordination with actin-mediated motion of an unmarked telomere. These and other findings highlight the importance of dynamic assembly/disassembly of telomere/LINC/actin ensembles and also suggest important roles for nuclear envelope deformations promoted by actin-mediated telomere/LINC movement. The presented low-SNR (signal-to-noise ratio) imaging methodology provides opportunities for future exploration of homolog pairing and related phenomena.